A computational characterization of CO@C60. Issue 11 (2nd November 2017) - Slanina, Zdeněk; Uhlík, Filip; Nagase, Shigeru; Akasaka, Takeshi; Adamowicz, Ludwik; Lu, Xing
ABSTRACT: The carbon monoxide encapsulation into C60 is evaluated using the DFT and MP2 calculations. The CO encapsulation is attractive, yielding an energy gain of more than 12 kcal/mol. This substantial encapsulation energy should produce at the conditions used in the high-temperature and high-pressure synthesis (originally used for encapsulation of rare gases in fullerenes) an equilibrium CO@C60 fraction of about 3.5% compared to the empty C60 . The computed IR and NMR spectra agree with the available observations for CO encapsulated into open-cage C60 derivatives.